2018
DOI: 10.2174/1567202615666180813130143
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-490-5P Targets CCND1 to Suppress Cellular Proliferation in Glioma Cells and Tissue Through Cell Cycle Arrest

Abstract: Overall, these results showed that epigenetic regulation of CCND1 via miR-490 was essential to glioma and provide a new insight into glioma diagnosis, treatment, prognosis and further translational investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…[16] In addition, the epigenetic negative regulation of CCND1 by microRNA-490 is the key to glioma, and it provides a new perspective for the diagnosis, treatment, prognosis, and further transformation of glioma. [17] In the present study, BSP showed no significant difference in methylation status of CCND1 promoter among cervical adenocarcinoma, cervical squamous cell carcinoma, and normal cervical tissues, being inconsistent with the results by Illumina (850K) or qRT-PCR. However, the methylation of CCND1 gene cannot be excluded from significant indicators of cervical adenocarcinoma, considering the small number of BSP samples and detection sites.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…[16] In addition, the epigenetic negative regulation of CCND1 by microRNA-490 is the key to glioma, and it provides a new perspective for the diagnosis, treatment, prognosis, and further transformation of glioma. [17] In the present study, BSP showed no significant difference in methylation status of CCND1 promoter among cervical adenocarcinoma, cervical squamous cell carcinoma, and normal cervical tissues, being inconsistent with the results by Illumina (850K) or qRT-PCR. However, the methylation of CCND1 gene cannot be excluded from significant indicators of cervical adenocarcinoma, considering the small number of BSP samples and detection sites.…”
Section: Discussioncontrasting
confidence: 94%
“…[16] It is proposed that the methylation status of paired box1 and SOX1 may be a new molecular marker for colorectal cancer screening. [17] There was a significant correlation between the down-regulation of SOX1 expression and the methylation of SOX1 promoter in primary hepatocellular carcinoma, and the methylation rate is 57.30%, being significantly higher than that in chronic hepatitis and cirrhosis. It is also discovered that DNA methylation levels of junctional adhesion moleculeA 3, SOX1, Slit guidance ligand 2, TTT, and C13ORF18 genes are significantly correlated with the prognosis of cervical intraepithelial neoplasia and can be used as predictors of cervical intraepithelial neoplasia prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…11 Low expression of miR-497-5p enhanced growth inhibition and apoptosis of glioma cells induced by TMZ, 12 however, Zhao et al demonstrated that miR-497-5p expression decreased glioma cell growth and invasion both in vitro and in vivo through Wnt3a/c-Jun feedback regulation. 13 Different from glioma, the function of miR-497-5p in other tumors is growth inhibition. For example, miR-497-5p can target YAP1 to inhibit the proliferation, invasion and migration of thyroid papillary carcinoma and non-small cell lung cancer, 14,15 and induce cycle arrest and apoptosis of breast cancer, gastric cancer, lung cancer and cervical cancer by regulating the expression of Bcl-w, Bcl-2, CDK6 or Cyclin E1.…”
Section: Introductionmentioning
confidence: 99%
“…MiR‐490 has a negative correlation with CCAT1 in NSCLC tissues, which is consistent with the findings of Zhao et al . in their study on glioma 28 . Overexpression of miR‐490 impaired H1299 cell viability and migration.…”
Section: Discussionmentioning
confidence: 92%